Pengaruh Tingkat Pendidikan, Tingkat Pendapatan, Kesadaran dan Pengetahuan Pajak Terhadap Kepatuhan Wajib Pajak Membayar Pajak Bumi dan Bangunan di Desa Kelungkung Kecamatan Batulanteh - Afrilia, Suma; Jibrail, Ahmad (EKALAYA : Jurnal Ekonomi Akuntansi, 2024)
This study aims to examine the effect of education level, income level, taxpayer awareness and knowledge of taxation on taxpayer compliance in paying land and building taxes in Kelungkung Village. This study uses a quantitative method. The population used in this study were taxpayers in Kelungkung Village, Batulanteh District. Sampling using the slovin formula. The data collection method used a questionnaire which was distributed directly to the respondents who were determined then analyzed the data using the SPSS version 25 application program. The results of this study indicate that the variable level of education has a negative effect on taxpayer compliance paying land and building taxes, income level has a positive and significant effect on compliance Taxpayers pay land and building tax, taxpayer awareness has a positive and significant effect on taxpayer compliance paying land and building tax, tax knowledge has a negative effect on taxpayer compliance paying land and building tax and education level, income level, awareness and knowledge of taxation have an effect simultaneously and significantly towards taxpayer compliance in paying land and building taxes.